Numerical Simulation of Corrugated Core Sandwich Construction for Biomedical Applications - Gobalan, Kreeshanthini; Subramaniyan, S Kanna (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Sandwich structures are lightweight composite structures with multiple functions, consisting of a lower-density core sandwiched between two thin hard facings. The model was created using SolidWorks software. The model created has a 5 x 3 cells of geometric model with a 1mm thick panel. It was built with three different core thicknesses which are 0.28mm, 0.49mm, and 0.7mm. The structure was subjected to a 400N force at the top surface and a fixed support at the bottom panel. The material used is Titanium Ti-6AI-4V, which is suitable for implantation. The study also compares the existing structure and the study structure in terms of maximum principal stress and core thickness relative to structure mass. The maximum stress for the sinusoidal corrugated structure with a core thickness of 0.28mm is 887.85 MPa. Thereby, the model made from 0.28mm core thickness is considered as a good structure because attributed by higher maximum stress value when compared than the other models. Besides, the results for the comparison of core thickness and the mass shows that as the thickness of the core increases the mass of the structure will also increases. Therefore, sinusoidal structure would serve as a potential use for vertebral implantation, ensuring its lightness where it is one of the factors for implantation and it is lighter.